2016
DOI: 10.1063/1.4960956
|View full text |Cite
|
Sign up to set email alerts
|

Unifying the rotational and permutation symmetry of nuclear spin states: Schur-Weyl duality in molecular physics

Abstract: In modern physics and chemistry concerned with many-body systems, one of the mainstays is identical-particle-permutation symmetry. In particular, both the intra-molecular dynamics of a single molecule and the inter-molecular dynamics associated, for example, with reactive molecular collisions are strongly affected by selection rules originating in nuclear-permutation symmetry operations being applied to the total internal wavefunctions, including nuclear spin, of the molecules involved. We propose here a gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…By being able to converge the zero-point energies and wave functions with smaller ensembles, we were able to show that for the protonated water systems, the ensemble sizes used in previous studies are likely not large enough to obtain accurate ground state properties. , With the approach validated and the savings that were achieved we are positioned to explore larger cluster ions, specifically H + (H 2 O) 5,6 where experimental studies have demonstrated that multiple isomers are sampled in the low-temperature experiments, and the most stable forms appear to be affected by partial deuteration. , The ability to separate the CH stretch vibrations from the lower-frequency motions in CH 5 + also provides an opportunity to further explore the five-dimensional rotor model, which was successfully used by Schlemmer and co-workers to analyze their rotationally resolved spectrum. …”
Section: Discussionmentioning
confidence: 99%
“…By being able to converge the zero-point energies and wave functions with smaller ensembles, we were able to show that for the protonated water systems, the ensemble sizes used in previous studies are likely not large enough to obtain accurate ground state properties. , With the approach validated and the savings that were achieved we are positioned to explore larger cluster ions, specifically H + (H 2 O) 5,6 where experimental studies have demonstrated that multiple isomers are sampled in the low-temperature experiments, and the most stable forms appear to be affected by partial deuteration. , The ability to separate the CH stretch vibrations from the lower-frequency motions in CH 5 + also provides an opportunity to further explore the five-dimensional rotor model, which was successfully used by Schlemmer and co-workers to analyze their rotationally resolved spectrum. …”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of deuterium nuclei (bosons), the one-to-one correspondence between the nuclear-spin angular momentum and the permutation symmetry breaks down. A new method unifying the rotational and permutation symmetries was proposed recently (Schmiedt, Jensen & Schlemmer 2016).…”
Section: A P P E N D I X B : T H E Ugan C H E M I C a L N E T W O R Kmentioning
confidence: 99%
“…Through these observations we obtain a homogenous data set pertaining to a quiescent region, presumably characterised by a simple physical structure, where comparison with chemistry models is more straightforward than in a star-forming core. The observations are interpreted by modelling the chemi-1 Schmiedt et al (2016) have recently shown that the spin angular momentum and the permutation symmetry are, after all, inherently coupled, and that it is possible to construct an unequivocal and practical representation for each spin angular momentum -symmetry species using the Young diagrams. In the present study, chemical species are distinguished solely by their nuclear spin symmetries.…”
Section: Introductionmentioning
confidence: 99%
“…Schmiedt et al (2016) have recently shown that the spin angular momentum and the permutation symmetry are, after all, inherently coupled, and that it is possible to construct an unequivocal and practical representation for each spin angular momentum -symmetry species using the Young diagrams. In the present study, chemical species are distinguished solely by their nuclear spin symmetries.…”
mentioning
confidence: 99%